ENERGY MANAGEMENT AND ACTIVE POWER CONTROL OF A HYDRID DISTRIBUTED GENERATION USING GENETIC ALGORITHM - P.K , Olulope (International Journal of Research -GRANTHAALAYAH, 2018)
The possibility of meeting the load demands and manage the energy of Okesha, Ado-Ekiti, Ekiti State, Nigeria using a hybrid system of power generation consisting of Wind/Solar PV energy sources in conjunction with the battery energy storage (Fuel cells) which act as a backup to the system is presented. The control mechanism is done through the use of genetic algorithm to optimally allocate the load and to control the charging and discharging of the battery. The results shows that the hybrid energy system through the control mechanism was able manage the energy generated so as to provide sufficient power to meet the optimum needs of the citizen of Okesha area in Ado Ekiti.